Differential Temporal and Spatial Preservation of Archaeological Sites in a Great Lakes Coastal Zone. Issue 3 (20th July 2012) - Lovis, William A.; Monaghan, G. William; Arbogast, Alan F.; Forman, Steven L.
Abstract: Analysis of regional site taphonomy that incorporates depositional and postdepositional histories has become increasingly important in understanding the nature of preserved site populations and the strategies necessary for their discovery. We applied a systematic archival and field strategy directed at understanding such taphonomic processes in the coastal sand dunes of the northern and eastern Lake Michigan basin, and coupled these with a tactically directed program of OSL, 14C, and AMS dating. We demonstrate that long-term geological processes including lake level variation, episodic dune activation and stabilization, and the long-term effects of postglacial isostatic adjustments have markedly affected the potential for preservation of sites in coastal dune contexts over time and across subregions of the basin. Preservation potential for different time periods in coastal dunes is largely not synchronous with that of southern Michigan floodplains, posing substantial inferential problems. The archaeology of coastal dunes specifically, and coastal zones generally, must be used with extreme caution when cast against archaeological data from landforms with different formation processes and histories. While particularly true for the Great Lakes region, these results have implications for regional research broadly.